Role of Peripheral Blood Regulatory T Cells and IL-2 in the Collateral Circulation of Acute Ischemic Stroke - Zhang S; Rao C; Wen M; Zhang X; Zha Z; Gu T; Zhu L; Yu C (International Journal of General Medicine)
Simin Zhang,1,2,* Chen Rao,1,2,* Meihai Wen,3 Xuke Zhang,3 Zhiwen Zha,1,2 Tong Gu,1,2 Lei Zhu,1,2 Chuanqing Yu1,2 1The Medical School of Anhui University of Science & Technology, Huainan, Anhui Province, 232000, People’s Republic of China; 2Department of Neurology, The First Hospital of Anhui University of Science & Technology (The First People’s Hospital of Huainan), Huainan, Anhui Province, 232000, People’s Republic of China; 3Bengbu Medical University, Bengbu, Anhui Province, 233000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chuanqing Yu; Lei Zhu, Email yuchuanqin1967@163.com; salimai@126.comBackground: Inflammation is recognized as a pivotal factor in the pathophysiology of acute ischemic stroke (AIS) and has the potential to influence the collateral circulation of patients. The objective of this investigation was to explore the link between peripheral regulatory T cells (Tregs), interleukin-2 (IL-2), and the status of collateral circulation.Methods: Between September 2023 and May 2024, the study incorporated 117 AIS patients from the neurology department, with 60 identified as having good collateral status (GCS) and 57 with poor collateral status (PCS). Additionally, a control group of 46 healthy individuals was included. Collateral circulation in AIS patients was assessed via computed tomography angiography. The levels of peripheral blood Tregs were quantified through flow cytometry, while IL-2 was measured by ELISA.Results: In this investigation, patients diagnosed with PCS demonstrated reduced Tregs (5.77 ± 1.55%) and IL-2 levels (7.37 ± 2.61 pg/mL) compared to individuals with GCS (7.09 ± 1.32%, 9.95 ± 3.58 pg/mL) and healthy controls (7.17 ± 1.40%,10.33 ± 4.01 pg/mL). Logistic regression analysis identified significant associations between Tregs and IL-2 levels and collateral circulation status (p< 0.05), with diminished levels of both being independent predictors of PCS when compared to GCS. A nomogram was developed to forecast risk factors for collateral circulation, further highlighting the potential of plasma Tregs and IL-2 levels as biomarkers in predicting collateral circulation among AIS patients. The diagnostic performance of Tregs and IL-2 was assessed utilizing receiver operating characteristic (ROC) analysis. The area under the ROC curve (AUC) for Tregs in differentiating GCS from PCS patients was ascertained to be 0.741 (95% confidence interval [CI]: 0.652– 0.830), while for IL-2, it was 0.710 (95% CI: 0.618– 0.803). Moreover, the combined measurement of Tregs and IL-2 resulted in an AUC of 0.779 (95% CI: 0.695– 0.863).Conclusion: Plasma levels of peripheral blood Tregs and IL-2 may function as promising biomarkers for the prediction of collateral circulation status, suggesting potential new therapeutic approaches aimed at enhancing cerebral collateral circulation, and providing new therapeutic targets for acute ischemic stroke. Keywords: acute ischemic stroke, collateral circulation, interleukin-2, neuroinflammation, regulatory T cells